2021
DOI: 10.12688/f1000research.74009.1
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Asymptomatic COVID-19 patient with a subtle hypercoagulable state and fluctuating D-dimer level

Abstract: Background: COVID-19 can infect an asymptomatic person silently without any overt symptoms despite diffuse blood clots throughout the body. Clot formation is induced by COVID-19 associated coagulopathy that can cause a high mortality rate. D-dimer, a fairly decisive marker for the coagulopathy event, is physiologically a marker of the fibrinolysis process. The increase of D-dimers in COVID-19 cases must be followed up because it relates to the initiation of a cytokine storm. Case presentation: We report an asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…4–6,20–24 These alterations have mainly been observed and are more pronounced in symptomatic patients with moderate or severe disease, 25 but they have also been described in asymptomatic infections. 26–28 This would explain the excess of bleeding complications after revascularization treatment in patients with both S-COVID and AS-COVID.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4–6,20–24 These alterations have mainly been observed and are more pronounced in symptomatic patients with moderate or severe disease, 25 but they have also been described in asymptomatic infections. 26–28 This would explain the excess of bleeding complications after revascularization treatment in patients with both S-COVID and AS-COVID.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][20][21][22][23][24] These alterations have mainly been observed and are more pronounced in symptomatic patients with moderate or severe disease, 25 but they have also been described in asymptomatic infections. [26][27][28] This would explain the excess of bleeding complications after revascularization treatment in patients with both S-COVID and AS-COVID. The same biologic changes that increase the risk of bleeding in patients with COVID-19 also result in a higher clot burden, microvascular thromboinflammation, and endothelitis with subsequent impaired posttreatment reperfusion, thereby increasing the risk of stroke recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Caesario et al reported a sudden elevation of D-dimer in an asymptomatic COVID-19 patient, which became normal with three days of heparin administration and rebounded back some days after anticoagulant therapy was stopped. They concluded that asymptomatic COVID-19 patients might also be at risk of a coagulopathy impairment [ 18 ]. Mahardhika et al also reported a high D-dimer level in an asymptomatic woman who was later confirmed to be positive for COVID-19 [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical scenarios such as planned procedures and bleeding often necessitate holding anticoagulation in patients on ECMO support (4). Surveillance of oxygenators during ongoing ECMO therapy to predict clot formation to avoid critical situations such as circuit failure and thrombus embolization is thus pertinent (5,6). Although monitoring circuit pressures may serve as a guide to ongoing hemodynamic changes, they cannot be solely relied upon since they may be misleading as seen in this case scenario.…”
Section: Commentmentioning
confidence: 99%